A Qualitative Study on Job Satisfaction among Blind and Visually Impaired Employees - Wong, Huey Siew (Open University Malaysia (OUM), 2017)
Studies related to job satisfaction among employees with Blind and Visual Impairments (BVI) had been given less attention by researchers either locally or internationally. The objectives of this study were to investigate how employees with BVI perceived their job satisfaction, examine factors that lead to job satisfaction and causes of job dissatisfaction. A total of 12 respondents working in public sector, semigovernment, private and NGO in the Klang Valley took part in this qualitative study. The data collected were through semi-structure and phone interview. Overall, the results demonstrated that BVI employees generally satisfied with their work. The research finding also indicated that factors which could lead to job satisfaction were relationships with colleagues, salary, benefits, recognition, physical conditions at work place, and working conditions within the company., Finally, the study found that causes of job dissatisfaction include feeling lonely and isolated; the management likes to see their disability rather than their abilities, no promotion opportunities, co-workers felt that they just need a job and salary, and no training is given. (Abstract by author)